Second chances in New Port Stephen : a novel - Alexander, T. J. (Emily Bestler Books/Atria, 2023)
Returning home to New Port Stephen, Florida, for Christmas after his career goes south, trans TV writer and comedian Eli Ward reconnects with his high school ex and they must decide whether to leave the past in the past or move on together.